2019
DOI: 10.3390/ijms20236092
|View full text |Cite
|
Sign up to set email alerts
|

DNA Oxidation and Excision Repair Pathways

Abstract: The physiological impact of the aberrant oxidation products on genomic DNA were demonstrated by embryonic lethality or the cancer susceptibility and/or neurological symptoms of animal impaired in the base excision repair (BER); the major pathway to maintain genomic integrity against non-bulky DNA oxidation. However, growing evidence suggests that other DNA repair pathways or factors that are not primarily associated with the classical BER pathway are also actively involved in the mitigation of oxidative assaul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 83 publications
0
57
0
2
Order By: Relevance
“…On the other hand, mitochondrial dysfunction in MGRN1-KO cells likely augments the production of reactive oxygen species (ROS), leading to higher oxidative stress [ 7 ]. In DNA, ROS predominantly damage bases or deoxirribose, with 8-oxo-7,8-dihydroguanine (8-oxodG) as the main oxidation product [ 44 ]. We compared the levels of 8-oxodG in melan-a6 and Mgrn1 -KO clones.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, mitochondrial dysfunction in MGRN1-KO cells likely augments the production of reactive oxygen species (ROS), leading to higher oxidative stress [ 7 ]. In DNA, ROS predominantly damage bases or deoxirribose, with 8-oxo-7,8-dihydroguanine (8-oxodG) as the main oxidation product [ 44 ]. We compared the levels of 8-oxodG in melan-a6 and Mgrn1 -KO clones.…”
Section: Resultsmentioning
confidence: 99%
“…No statistical significance was found in BER-DRC based on the pathologic stage of the tumors and the expression levels of BER genes did not correlate with BER-DRC [86]. Current reports suggest that oxidative DNA damage may be removed from DNA also via NER [87,88] and the authors postulate that loss of NER function shares common features arising from BER defects, including cancer predisposition [89]. Despite we have recorded significantly higher NER DRC in tumor tissue from CRC patients in comparison to adjacent mucosa, we fail to ascribe this change to any specific DNA damage [86].…”
Section: Base Excision Repair Capacity In Sporadic Colorectal Cancermentioning
confidence: 92%
“…Studies on the molecular mechanisms of the susceptibility to cutaneous malignant melanoma genes have suggested that this susceptibility is associated with sequence variation mutations in NER genes ( 2 , 24 ). Mutated XPD may be a biomarker of skin malignant melanoma ( 1 ). Kertat et al ( 25 ) revealed that the Gln/Gln genotype of the XPD 751 codon is a genetic marker of male malignant melanoma, and that the Lys/Gln genotype is important for predicting tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…UV radiation, smoking and various other environmental factors can cause DNA damage (1). In the human body, DNA damage can be corrected by direct repair, base excision repair and nucleotide excision repair (NER) to maintain genome stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation